Polymorphism of Bovine Growth Hormone Receptor Gene (g.3338A>G) and Its Association with Body Measurements and Body Weight in Pasundan Cows - W. P. B. Putra; P. P. Agung; S. Anwar; S. Said (Faculty of Animal Science, Bogor Agricultural University, 2019)
Bovine growth hormone receptor (bGHR) gene was one of the growth hormone family genes that important for body growth and development of cattle. This research was carried out to identify the polymorphism in the exon 10 of bGHR gene from 142 heads of Pasundan cows at West Java and its association with body length (BL), withers height (WH), heart girth (HG), and body weight (BW). There are two mutation points in the bGHR gene based on the sequencing analysis i.e. g.3322del.A and g.3338A>G. The single nucleotide polymorphism (SNP) at g.3338A>G was detected using PCR-RFLP method with AluI restriction enzyme and showed three genotypes of AA (0.49), AG (0.37), and GG (0.14). The allelic frequencies were 0.67 (A) and 0.33 (G). The number of allele effective (ne) value was 1.79 and described that A allele was the higher allele in the bGHR gene in this study. The polymorphic informative content (PIC) value was 0.34 and categorized as a moderate category. The Chi-square (χ2) analysis showed that the population sample was in the Hardy-Weinberg equilibrium (χ2<5.99). It was concluded that the polymorphism of bGHR gene had a significant association (p<0.05) with BL, WH, and BW of Pasundan cows. Research showed that all body measurements in GG genotype animals were lowest than other genotypes. Meanwhile, the highest of BW was showed in GG genotype. In addition, the average of BL, WH, HG, and BW in Pasundan cows (2 PPI and 3PPI) were 126.88±14.25 cm; 133.97±31.69 cm; 145.35±13.56 cm and 201.85±44.87 kg, respectively.